2011
DOI: 10.1029/2010wr009561
|View full text |Cite
|
Sign up to set email alerts
|

On the interaction between bathymetry and climate in the system dynamics and preferred levels of the Great Salt Lake

Abstract: The Great Salt Lake is a terminal lake whose level is determined by the balance between inflows and outflows. We examine the causes for multimodality in the distributions of lake level and hence volume and area that have previously been examined from a system dynamics perspective. We focus on the role of bathymetry in the dynamics of this system and show that some of the modes that are observed and that represent preferred system states are attributable to features of the bathymetry described using the topogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 31 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…As salinity increases in saline lakes, the ratio of evaporation rate from saline water to fresh water (E sal /E fw ) decreases (Calder and Neal, 1984;Harbeck, 1955;Mohammed and Tarboton, 2011). This salinity effect dominates effects due to temperature changes (Harbeck, 1955), so that a first order approximation of the salinity effect on E sal /E fw can be determined from salinity alone.…”
Section: Determining the Effect Of Salinity On Lake Evaporationmentioning
confidence: 97%
“…As salinity increases in saline lakes, the ratio of evaporation rate from saline water to fresh water (E sal /E fw ) decreases (Calder and Neal, 1984;Harbeck, 1955;Mohammed and Tarboton, 2011). This salinity effect dominates effects due to temperature changes (Harbeck, 1955), so that a first order approximation of the salinity effect on E sal /E fw can be determined from salinity alone.…”
Section: Determining the Effect Of Salinity On Lake Evaporationmentioning
confidence: 97%
“…In other words, lake volume changes are sensitive to changes in precipitation, streamflow and evaporation. Evaporation and precipitation are also modulated by lake area, which varies in response to the system dynamics involving the bathymetry relationships between volume, area and level [ Mohammed and Tarboton , 2011]. Two questions then arise: is lake volume change equally sensitive to precipitation, streamflow and evaporation or not and which variable among precipitation, streamflow or evaporation could influence the lake volume the most?…”
Section: Great Salt Lake Sensitivitymentioning
confidence: 99%
“…The volume of the Great Salt Lake fluctuates with its level, resulting in concentration or dilution of the salt in the lake, affecting surface salinity. Water residence time in the lake is about 5 years, which is also the time scale implied by the historical range of volume changes (active volume) in comparison to mean inflows [ Mohammed and Tarboton , 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Both modes remained within the dry subhumid moisture class in the Thornthwaite classification (−33 ≤ IM100 ≤ 0; Grundstein ), although the change in IM100 from −23.6 for mode 1 to −10.0 for mode 2 shifted the station from the more arid to the less arid limit of that class. Mohammed and Tarboton () reported that the frequency distribution of lake levels in terminal lakes can display preferred states due to the multimodality of hydrological forcing which are then translated into a lake‐level frequency distribution by lake bathymetry. The histogram of historical lake volumes reported by Todhunter and Fietzek‐DeVries () further illustrate these hydroclimatic modes.…”
Section: Discussionmentioning
confidence: 99%